Stoichiometric δ‐NbN: The Most Incompressible Cubic Transition Metal Mononitride. Issue 11 (24th August 2017) - Tan, Jiao; Zhang, Shihao; Wang, Shanmin; Wang, Wendan; Zheng, Xu; Zhao, Jianfa; Li, Wenmin; Mao, Xiaochun; Liu, Ke; Zhou, Xiaolin; Zhao, Yusheng; Jin, Changqing; et al.
Abstract : We report the high‐pressure synthesis and elastic properties of stoichiometric cubic δ‐NbN investigated by a combination of experiments and first principles calculations. Using the high pressure solid‐state ion‐exchange reaction route, we have successfully synthesized polycrystalline δ‐NbN at 5.5 GPa and 1673 K. The refined lattice parameter of as‐synthesized sample is 4.3960(6) Å, corresponding to the stoichiometric niobium nitride. The determined bulk modulus of δ‐NbN is B 0  = 319(2) GPa with B ′ 0  = 4.4(2), which is one of the most incompressible cubic transition metal mononitrides. Theoretical calculations of the elastic constants, bulk modulus, shear modulus, Young's modulus, and Poisson's ratio agree well with experimental and previous theoretical results. The calculated minimum shear strength of δ‐NbN is 23.4 GPa for the (111) [ 1 ¯ 1 ¯ 2 ] slip system, comparable to those of ZrN and HfN. In addition, a finite density of states at the Fermi level was revealed for δ‐NbN, hence exhibiting metallic behavior. Abstract : Tan et al. report the synthesis of stoichiometric niobium nitride from high pressure solid‐state ion‐exchange reaction route. With stoichiometric sample and under hydrostatic pressure condition, the accurate bulk modulus of δ‐NbN has been measured as 319(2) GPa by high pressure synchrotron XRD experiments. Simultaneously, the elastic properties, plastic shear strength, energy band structure and partial density of states have been further calculated.